The Impact of Dietary Knowledge on Health: Evidence from the China Health and Nutrition Survey - Sun, Yangyang (Int J Environ Res Public Health, 2021)
Promoting a healthy diet through education is part of the Healthy China 2030 action plan. However, studies examining how dietary knowledge affects public health in China are sparse. This study employs multiple waves of the China Health and Nutrition Survey (CHNS) data to examine the impacts of dietary knowledge on Chinese adults’ health, with a particular emphasis on how the impacts of dietary knowledge vary across different demographic groups. Moreover, we contribute to the literature by incorporating the spouse’s dietary knowledge into the analysis framework to inspect the relationship between a spouse’s dietary knowledge and an individual’s health. Our results indicate that dietary knowledge significantly improves an individual’s health status. However, there is no evidence that an individual’s health is influenced by his/her spouse’s dietary knowledge. Moreover, we find that individuals with a lower level of education and rural residents benefit more from increasing dietary knowledge. Policy implications of this study are also discussed.